Potential Role of Cannabinoid Type 2 Receptors in Neuropsychiatric and Neurodegenerative Disorders - Ishiguro, Hiroki; Kibret, Berhanu Geresu; Horiuchi, Yasue; Onaivi, Emmanuel S. (Frontiers in Psychiatry, 2022)
The endocannabinoid system (ECS) is composed of the two canonical receptor subtypes cannabinoid type 1 receptor (CB1R) and type 2 receptor (CB2R), endocannabinoids (eCBs) and enzymes responsible for the synthesis and degradation of eCBs. Recently, with the identification of additional lipid mediators, enzymes and receptors, the expanded ECS called the endocannabinoidome (eCBome) has been presented. Activation of CB1R is associated with central nervous system (CNS) side effects, whereas, CB2R activation is devoid of such effects and hence CB2Rs might be utilized as a new target for the treatment of different disorders including neuropsychiatric disorders. Previous studies suggested that CB2Rs were absent in the brain and they were considered as “peripheral” receptors, however, recent studies confirmed the presence of CB2Rs in different brain region. Several studies have now focused on the characterization of its physiological and pathological roles. Studies done on the role of CB2Rs as a therapeutic target for treating different disorders revealed important putative role of CB2R in neuropsychiatric disorders that requires further clinical validation. This review addresses recent advances on the role of CB2Rs in neuropsychiatric and neurodegenerative disorders including, but not limited to, anxiety, depression, schizophrenia, Parkinson’s disease (PD), Alzheimer’s disease (AD), Huntington’s disease (HD) and addiction.